Biological studies of insect herbivores associated with some species of Solanum L - Olckers, Terence (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1989)
Solanum mauritianum Scop. (bugweed), a serious exotic weed in South Africa, supports a depauperate herbivore fauna relative to indigenous Solanum species. These comprise mainly polyphagous, and some oligophagous, species. The greater diversity of insect herbivores on Solanum hermannii Dun., relative to other indigenous Solanum species in the eastern Cape, suggests that the plant is indigenous and not exotic as has been suggested. Five oligophagous species seasonally caused a high incidence of damage to S.hermannii and other indigenous Solanum species in the eastern Cape, during the study period. Galls of the flowers, stems and leaves of some indigenous Solanum plants are described and biological data on the gall-formers and their natural enemies presented. The tortoise beetle, (Chrysomelidae), defoliates a Conchyloctenia tigrina wide range of indigenous Olivo Solanum species. The exotic S.mauritianum and S.elaeagnifolium Cav. were unfavourable for growth and survival. S.hermannii proved the most favourable of the indigenous hosts tested, for growth and survival, providing further evidence that it is indigenous. Extensive studies on different field populations of the beetle revealed no evidence of host adaptation (host races). All populations tested displayed greater fitness when reared on S.hermannii. South African Solanum faunas are characterized by a scarcity of endophagous and monophagous herbivores, vacant feeding niches and low numbers of species relative to other plant taxa. This may suggest evolutionary immaturity of the insect-plant associations, although comparative studies of solanums from other parts of the world are needed for confirmation. Alternatively, these characteristics may simply be a feature of the genus Solanum in general. The depauperate herbivore fauna of S.mauritianum reflects a lack of local herbivores suitably preadapted to overcome its defences. This appears to be accentuated by absence of any close relatives of bugweed in South Africa. The greater diversity of herbivores in its native South America suggests that biological control may be a potentially useful means of control for bugweed. The potential for biological control is, however, threatened by the susceptability of the cultivated eggplant (Solanum melongena L.) to attack by Solanum-feeding insects. Possible solutions to this problem are discussed
Keywords: Solanum -- Control -- South Africa; Phytophagous insects -- South Africa